Step
*
1
of Lemma
monotone-bar-induction3
1. B : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
2. Q : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
3. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s] 
⇒ (∀m:ℕ. B[n + 1;s.m@n]))
4. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s] 
⇒ ⇃(Q[n;s]))
5. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  ((∀m:ℕ. ⇃(Q[n + 1;s.m@n])) 
⇒ ⇃(Q[n;s]))
6. bar : ∀alpha:ℕ ⟶ ℕ. ⇃(∃m:ℕ. B[m;alpha])
7. ⇃(∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
      ∀f:ℕ ⟶ ℕ
        ∃n:ℕ. ∃k:ℕn. ((B k f) ∧ ((M n f) = (inl k) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl k) ∈ (ℕ?))))))
⊢ ⇃(⇃(Q[0;λx.⊥]))
BY
{ Assert ⌜(∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
            ∀f:ℕ ⟶ ℕ
              ∃n:ℕ
               ∃k:ℕn. ((B k f) ∧ ((M n f) = (inl k) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl k) ∈ (ℕ?))))))
          
⇒ ⇃(Q[0;λx.⊥])⌝⋅ }
1
.....assertion..... 
1. B : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
2. Q : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
3. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s] 
⇒ (∀m:ℕ. B[n + 1;s.m@n]))
4. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s] 
⇒ ⇃(Q[n;s]))
5. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  ((∀m:ℕ. ⇃(Q[n + 1;s.m@n])) 
⇒ ⇃(Q[n;s]))
6. bar : ∀alpha:ℕ ⟶ ℕ. ⇃(∃m:ℕ. B[m;alpha])
7. ⇃(∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
      ∀f:ℕ ⟶ ℕ
        ∃n:ℕ. ∃k:ℕn. ((B k f) ∧ ((M n f) = (inl k) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl k) ∈ (ℕ?))))))
⊢ (∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
    ∀f:ℕ ⟶ ℕ
      ∃n:ℕ. ∃k:ℕn. ((B k f) ∧ ((M n f) = (inl k) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl k) ∈ (ℕ?))))))
⇒ ⇃(Q[0;λx.⊥])
2
1. B : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
2. Q : n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ ℙ
3. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s] 
⇒ (∀m:ℕ. B[n + 1;s.m@n]))
4. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  (B[n;s] 
⇒ ⇃(Q[n;s]))
5. ∀n:ℕ. ∀s:ℕn ⟶ ℕ.  ((∀m:ℕ. ⇃(Q[n + 1;s.m@n])) 
⇒ ⇃(Q[n;s]))
6. bar : ∀alpha:ℕ ⟶ ℕ. ⇃(∃m:ℕ. B[m;alpha])
7. ⇃(∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
      ∀f:ℕ ⟶ ℕ
        ∃n:ℕ. ∃k:ℕn. ((B k f) ∧ ((M n f) = (inl k) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl k) ∈ (ℕ?))))))
8. (∃M:n:ℕ ⟶ (ℕn ⟶ ℕ) ⟶ (ℕn?)
     ∀f:ℕ ⟶ ℕ
       ∃n:ℕ. ∃k:ℕn. ((B k f) ∧ ((M n f) = (inl k) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ ((M m f) = (inl k) ∈ (ℕ?))))))
⇒ ⇃(Q[0;λx.⊥])
⊢ ⇃(⇃(Q[0;λx.⊥]))
Latex:
Latex:
1.  B  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbP{}
2.  Q  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbP{}
3.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}.    (B[n;s]  {}\mRightarrow{}  (\mforall{}m:\mBbbN{}.  B[n  +  1;s.m@n]))
4.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}.    (B[n;s]  {}\mRightarrow{}  \00D9(Q[n;s]))
5.  \mforall{}n:\mBbbN{}.  \mforall{}s:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}.    ((\mforall{}m:\mBbbN{}.  \00D9(Q[n  +  1;s.m@n]))  {}\mRightarrow{}  \00D9(Q[n;s]))
6.  bar  :  \mforall{}alpha:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.  \00D9(\mexists{}m:\mBbbN{}.  B[m;alpha])
7.  \00D9(\mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  (\mBbbN{}n?)
            \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}
                \mexists{}n:\mBbbN{}
                  \mexists{}k:\mBbbN{}n.  ((B  k  f)  \mwedge{}  ((M  n  f)  =  (inl  k))  \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  ((M  m  f)  =  (inl  k))))))
\mvdash{}  \00D9(\00D9(Q[0;\mlambda{}x.\mbot{}]))
By
Latex:
Assert  \mkleeneopen{}(\mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  (\mBbbN{}n?)
                    \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}
                        \mexists{}n:\mBbbN{}
                          \mexists{}k:\mBbbN{}n
                            ((B  k  f)  \mwedge{}  ((M  n  f)  =  (inl  k))  \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  ((M  m  f)  =  (inl  k))))))
                {}\mRightarrow{}  \00D9(Q[0;\mlambda{}x.\mbot{}])\mkleeneclose{}\mcdot{}
Home
Index